2014
DOI: 10.1002/2013gl058650
|View full text |Cite
|
Sign up to set email alerts
|

Changes in global ocean wave heights as projected using multimodel CMIP5 simulations

Abstract: Ocean surface waves can be major hazards in coastal and offshore activities. However, there exists very limited information on ocean wave behavior in response to climate change, because such information is not simulated in current global climate models. This study made statistical projections of changes in ocean wave heights using sea level pressure (SLP) information from 20 CMIP5 (Coupled Model Intercomparison Project Phase 5) global climate models for the 21st century. The results show significant wave heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
155
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 22 publications
(33 reference statements)
12
155
2
2
Order By: Relevance
“…However for example, studies such as those by the Coordinated Ocean Wave Climate Project (COWCLIP) (Hemer et al, 2013b) predict a reduction in mean annual, spring and summer SWH in the Northeast Atlantic by the end of the 21st century, consistent with the study presented in this paper. Global projections using CMIP5 models under the RCP4.5 and RCP8.5 emission scenarios (Dobrynin et al, 2012) and a 20-member ensemble of statistically modelled projections derived from CMIP5 data (Wang et al, 2014) also show a decrease in mean annual SWH for Atlantic mid-latitudes.…”
Section: Introductionmentioning
confidence: 92%
“…However for example, studies such as those by the Coordinated Ocean Wave Climate Project (COWCLIP) (Hemer et al, 2013b) predict a reduction in mean annual, spring and summer SWH in the Northeast Atlantic by the end of the 21st century, consistent with the study presented in this paper. Global projections using CMIP5 models under the RCP4.5 and RCP8.5 emission scenarios (Dobrynin et al, 2012) and a 20-member ensemble of statistically modelled projections derived from CMIP5 data (Wang et al, 2014) also show a decrease in mean annual SWH for Atlantic mid-latitudes.…”
Section: Introductionmentioning
confidence: 92%
“…The few global studies discussing large-scale projections of waves in view of climate change mainly focus on average wave conditions [Hemer et al, 2013a]. In global studies changes in extreme wave conditions have been marginally explored by focusing on high percentile values or on low return levels [Mori et al, 2010;Hemer et al, 2013aHemer et al, , 2013bSemedo et al, 2013;Wang et al, 2014;Perez et al, 2015], omitting the rare extremes that may give rise to catastrophic impacts, although more detailed local studies exist [De Winter et al, 2012;Lionello et al, 2012;Casas-Prat and Sierra, 2013;Erikson et al, 2015;Shimura et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the identified trends in the extreme wave climate must be verified by other datasets before conclusions can be made. In particular, it has been demonstrated in previous studies that the effect of climate change on the wave climate is highly location dependent (Vanem 2014;Wang et al 2014). Therefore, the results from one arbitrary location cannot be used to confidently inform about climatic trends.…”
Section: Discussionmentioning
confidence: 99%
“…The climate scenario is obviously important, and only two future scenarios are considered in this study. However, studies have demonstrated that the choice of climate model might contribute more to the overall uncertainty of the future wave climate than the climate scenarios themselves (Wang and Swail 2006;Grabemann and Weisse 2008;Grabemann et al 2015;Wang et al 2012Wang et al , 2014see also de Winter et al 2013). Future projections of waves are typically obtained using wind output from climate models as input to numerical wave models, and also the choice of wave model, the downscaling method and the model resolution will have a big impact on the results.…”
Section: Introductionmentioning
confidence: 99%